Secretory response to secretin in a patient with diarrhoea and the Zollinger-Ellison pattern of gastric secretion. Issue 10 (October 1969) - Petersen, H.; Myren, J.; Liavåg, I.
Abstract : In a woman with diarrhoea and the Zollinger-Ellison pattern of gastric secretion, the secretion of fluid and bicarbonate into the duodenum in response to secretin was found to be significantly greater than in controls. No pancreatic tumour was found at operation. The pancreas was, however, larger than normal. The patient did not show symptoms of peptic ulcer disease until vagotomy and pyloroplasty had been performed. A capacity to secrete large amounts of bicarbonate was believed to be the explanation of why she was able to tolerate great amounts of acid.